Dehydration of lactate to acrylate using alkaline earth metal modified hydroxyapetite - Doke, Dhananjay S. S.; Dongre, Mohan K. K.; Umbarkar, Shubhangi B. B. (Catalysis Letters, 2024)
Acrylates/acrylic acid are important for polymer industry due to its very high volume applications in different sectors. Activity of Ba/Mg modified hydroxyapatite for vapour-phase dehydration of ammonium lactate with 100% conversion and 60% acrylate selectivity was attributed to fine tuning of acid/base properties and formation of surface Ba/Ca lactate species.
Keywords: acrylate; Alkaline earth metal; dehydration; Lactate; Modified hydroxyapetite